2007
DOI: 10.1111/j.1526-4610.2007.00863.x
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Migraine and the G1246A Polymorphism in the Hypocretin Receptor 2 Gene

Abstract: Our study does not support a major contribution of the HCRTR2 G1246A polymorphism to the pathogenesis of migraine in contrast to its effects in cluster headache.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…This association was confirmed by a large study performed in Germany, showing that homozygous carriers of the G allele had a twofold increase in risk for the disease [15], but was not replicated in a complex dataset of CH patients of Danish, Swedish, and British origin [16]. Conversely, analyzing the same polymorphism in migraine, no statistical difference was found between cases and controls [17] and the same results were obtained by an independent group [18]. Thereby, in order to deepen the analysis of hypocretin system in migraine pathogenesis, we hypothesized that HCRTR1 gene polymorphisms would modify the occurrence and the clinical features of migraine patients.…”
Section: Introductionmentioning
confidence: 82%
“…This association was confirmed by a large study performed in Germany, showing that homozygous carriers of the G allele had a twofold increase in risk for the disease [15], but was not replicated in a complex dataset of CH patients of Danish, Swedish, and British origin [16]. Conversely, analyzing the same polymorphism in migraine, no statistical difference was found between cases and controls [17] and the same results were obtained by an independent group [18]. Thereby, in order to deepen the analysis of hypocretin system in migraine pathogenesis, we hypothesized that HCRTR1 gene polymorphisms would modify the occurrence and the clinical features of migraine patients.…”
Section: Introductionmentioning
confidence: 82%
“…Some polymorphisms, including the well‐known G1246A, of the orexin2‐receptor have been linked to cluster headache in the majority of studies 15‐17 but not in all studies 18 and not to treatment response in cluster headache 19 . Studies on the same polymorphism in migraine did not reveal a significant association 20,21 . Another gene involved in circadian rhythmicity, the CLOCK gene with its T3111C polymorphism, has also not been linked to cluster headache 22 …”
Section: The Anatomy Of the Sleeping And Of The Headache Brainmentioning
confidence: 99%
“…Studies in CH patients prompted two independent research groups to evaluate the association of the G1246A polymorphisms in the HCRTR2 gene with migraine. Both studies found no association between this polymorphism and migraine or its clinical subtypes [88,89]. Recently, we performed a genetic case–control study to investigate whether genetic variants in the HCRTR1 gene could modify the occurrence and the clinical features of migraine.…”
Section: Reviewmentioning
confidence: 99%